A method for ultrasound probe calibration based on arbitrary wire phantom - Chunxu Shen (Taylor & Francis Group, 2019)
To create a freehand three-dimensional ultrasound system for image-guided intervention, ultrasound probe calibration process plays an important role. This paper introduces a novel method, based on arbitrary wire phantom, to achieve both spatial and temporal calibration for ultrasound probe. Spatial calibration is realized by solving an optimization problem established by the wires and corresponding intersections in ultrasound plane. Next, temporal calibration is achieved by processing ultrasound image sequence and the corresponding position of optical localizer mounted to ultrasound probe. In order to make up for the deficiency of geometry structure in arbitrary phantom, we develop a point-recognition algorithm to determine the correspondence between wires in phantom space and intersections in ultrasound image space. Extensive comparative experiment is conducted on N-wire phantom and our phantom in 20 independent trials to fully evaluate precision, accuracy, and robustness of proposed calibration method. Shallow probe experimental result shows that proposed method improves average calibration precision to 0.896 mm and accuracy to 1.022 mm, compared to 0.938 and 1.140 mm using N-wire, respectively. Further, we also perform extra independent trials to evaluate the impact of deep image for the proposed method. Result shows the precision ranges from 0.740 to 1.178 mm, and the accuracy ranges from 0.939 to 1.400 mm, which indicates proposed method is potential for probe calibration in ultrasound image-guided intervention.